Recovery of Corneal Endothelial Cells from Periphery after Injury. - Sang Ouk Choi; Hyun Sun Jeon; Joon Young Hyon; Yun-Jung Oh; Won Ryang Wee; Tae-Young Chung; Young Joo Shin; Jeong Won Kim (PLoS ONE, 2015)
Wound healing of the endothelium occurs through cell enlargement and migration. However, the peripheral corneal endothelium may act as a cell resource for the recovery of corneal endothelium in endothelial injury.To investigate the recovery process of corneal endothelial cells (CECs) from corneal endothelial injury.Three patients with unilateral chemical eye injuries, and 15 rabbit eyes with corneal endothelial chemical injuries were studied. Slit lamp examination, specular microscopy, and ultrasound pachymetry were performed immediately after chemical injury and 1, 3, 6, and 9 months later. The anterior chambers of eyes from New Zealand white rabbits were injected with 0.1 mL of 0.05 N NaOH for 10 min (NaOH group). Corneal edema was evaluated at day 1, 7, and 14. Vital staining was performed using alizarin red and trypan blue.Specular microscopy did not reveal any corneal endothelial cells immediately after injury. Corneal edema subsided from the periphery to the center, CEC density increased, and central corneal thickness decreased over time. In the animal study, corneal edema was greater in the NaOH group compared to the control at both day 1 and day 7. At day 1, no CECs were detected at the center and periphery of the corneas in the NaOH group. Two weeks after injury, small, hexagonal CECs were detected in peripheral cornea, while CECs in mid-periphery were large and non-hexagonal.CECs migrated from the periphery to the center of the cornea after endothelial injury. The peripheral corneal endothelium may act as a cell resource for the recovery of corneal endothelium.